Autonomous observations enhance our ability to observe the biological carbon pump across diverse carbon export regimes - Shawnee Traylor; David P. Nicholson; Samantha J. Clevenger; Ken O. Buesseler; Eric D'Asaro; Craig M. Lee (Limnology and Oceanography, 2025)
The expansion of autonomous observation platforms offers vast opportunities for analyzing ocean ecosystems and their role in carbon export. As part of the EXport Processes in the Ocean from RemoTe Sensing campaign, we autonomously measured the productivity regimes in two contrasting end‐member ecosystem states. The first campaign occurred in the subpolar North Pacific near Ocean Station Papa (Site 1), characterized by iron limitation and a highly regenerative regime. The second captured a springtime bloom in the North Atlantic (Site 2), which typically drives efficient export of productivity. Using a combination of floats and gliders carrying biogeochemical sensors, we quantified gross primary productivity, net community production, and organic carbon export potential ( f C org ) to assess biological carbon pump strength. Site 2 demonstrated higher cruise‐period productivity, with roughly 5× the gross primary productivity and 13× the euphotic zone net community production seen at Site 1. Greater export efficiency at Site 2 was reflected in numerous indices, such as the ratio of new production to net primary productivity ( ef ‐ratio; Site 1: 0.33; Site 2: 0.73), the ratio of sinking particulate organic carbon to net primary productivity ( ez ‐ratio; Site 1: 0.24; Site 2: 0.69), and mean daily f C org (Site 1: 3.4 ± 0.7; Site 2: 20.3 ± 2.3 mmol C m −2 d −1 ). Together with particulate organic carbon flux derived from thorium‐234 measurements, we infer that observed low net community production was almost entirely routed to sinking particulate organic carbon at Site 1, while the much higher net community production at Site 2 resulted in near‐equal proportions routed to dissolved organic carbon production and sinking particulate organic carbon.